Mirounga leonina - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Mirounga leonina (Linnaeus, 1758). Syst. Nat., 10th ed., 1:37. TYPE LOCALITY: Juan Fernandez Isis., Robinson Crusoe Isl. (Chile). DISTRIBUTION: Subantarctic islands, including Macquarie, Kerguelen, and S. Georgia Isis. Formerly Juan Fernandez Isis. PROTECTED STATUS: CITES - Appendix II. ISIS NUMBER: 5301413002008002001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 287, DOI: 10.5281/zenodo.7352980